Study persistence and academic achievement as a function of the type of competing tendencies - Lens, Willy (2005)
In order to understand and predict students' achievement and persistence at learning activities, many contemporary motivational models consider how much students are motivated for their school work. However, students' achievement and persistence might not only be affected by their amount of study motivation, but also by the motivation to engage in competing alternative activities, as suggested three decades ago by Atkinson and Birch in their "Dynamics of Action " (1970). Building on this line of theorizing, the present contribution indicates that it is not only instructive to consider the level of students' motivation for these competing activities, but also the type of activities they engage in, that is leisure vs. working activities. Two studies demonstrated that whereas time spent on working activities is inversely related to study motivation, attitude, persistence and academic achievement, such relationships were not found for leisure time engagement. Spending some time on leisure time activities does not interfere with optimal learning.